2023
DOI: 10.7759/cureus.33310
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Subclavian Steal Syndrome: A Novel Case of Vasculopathy

Abstract: Subclavian steal syndrome (SSS) refers to the phenomenon of retrograde flow in an ipsilateral branch of the subclavian artery due to hemodynamically significant stenosis or occlusion of the ipsilateral proximal subclavian artery. While SSS is usually asymptomatic, it can manifest as vertebrobasilar insufficiency (VBI), ischemia of the affected extremity, or cardiac angina when an internal mammary artery (IMA) is used as a bypass graft. The underlying etiology is most often atherosclerosis but can include Takay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…While most of the patients with the underlying condition remain asymptomatic, they can present with symptoms of VBI (dizziness while moving left arm), upper extremity claudication, or cardiac angina [2]. Symptomatic SSS presentation is more often seen in males over 50 years of age with a 2:1 male-to-female ratio [1,6]. The branching patterns of the aortic arch were studied by Popieluszko et al, in the meta-analysis of 23,882 adult aortic arches from 51 studies which showed that the most common branching pattern (from right to left), brachiocephalic trunk, the LCCA, and the LSCA with an overall incidence of 80.9% [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While most of the patients with the underlying condition remain asymptomatic, they can present with symptoms of VBI (dizziness while moving left arm), upper extremity claudication, or cardiac angina [2]. Symptomatic SSS presentation is more often seen in males over 50 years of age with a 2:1 male-to-female ratio [1,6]. The branching patterns of the aortic arch were studied by Popieluszko et al, in the meta-analysis of 23,882 adult aortic arches from 51 studies which showed that the most common branching pattern (from right to left), brachiocephalic trunk, the LCCA, and the LSCA with an overall incidence of 80.9% [7].…”
Section: Discussionmentioning
confidence: 99%
“…SSS is a condition associated with the reversal of blood flow in the ipsilateral vertebral artery due to hemodynamically significant stenosis or occlusion of the ipsilateral PSCA [ 1 , 2 ]. The incidence and prevalence of SSS are not very well defined due to asymptomatic presentation [ 6 ]. The studies have shown the incidence of subclavian artery occlusion of 17% and 9% of them were symptomatic [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations